Spillover effects of the Venezuelan crisis: Migration impacts in Colombia - Caruso, German; Canon, Christian Gomez; Mueller, Valerie (Oxford University Press, 2021)
In the wake of the Venezuelan crisis, Colombian migrants are returning to their place of birth. Since 2016, however, there has been a spike of immigration to Colombia attributable to inflows of the Venezuelan-born. Using high-frequency administrative data, we estimate the impacts of the recent labour supply shock–driven by the economic predicament in Venezuela–on the labour and poverty outcomes of native Colombians. We employ an instrumental variables approach to account for the selection of immigrants into locations with more or less desirable conditions. A 1 percentage point increase in immigration from Venezuela reduces informal sector wages by 10 percentage points in urban areas. As the crisis increased the fraction of migrants by 0.2 percentage points in 2017, we estimate urban wages decreased by a total of 2 percentage points. A dual-pronged approach is warranted to promote the economic assimilation of Venezuelans while protecting the job security of Colombians.